Evaluating the K-Cash Pilot Trial in Mutual Fund Transactions: A User-Centric Perspective - Afrindah Eka Ramadhani; Tubagus Muhammad Yusuf Khudri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the initial institutional user acceptance of the K-CASH (KSEI Cash Management System) during its pilot testing phase in mutual fund transactions. The initiative to develop K-CASH stems from the growing need to digitalize fund settlement processes that traditionally rely on virtual accounts, manual proof-of-transfer verification, and reconciliation procedures conducted by Custodian Banks, mechanisms that are susceptible to mismatches and may prolong the settlement cycle. The system, which is built upon the Investor Fund Unit Account (IFUA) structure, introduces real-time balance validation, automated fund locking, unit validation, and integrated settlement instructions through S-INVEST. Employing a qualitative case study approach, this research adopts the UTAUT framework, comprising performance expectancy, effort expectancy, social influence, and facilitating conditions, and the interview findings suggest the presence of behavioral intention among users. Data collection involved semi-structured interviews with five institutional users at PT X, complemented by pilot testing documentation. The findings indicate that users perceive K-CASH as a system with substantial potential to enhance operational efficiency by reducing reconciliation workloads and minimizing mismatches, despite the presence of several technical issues such as reporting filter errors. The system is generally considered user-friendly, supported by effective internal coordination and managerial endorsement. Regulatory influence was also identified as a critical driver of participation, positioning PT X as an early institutional adopter. Nonetheless, the study identifies significant external gaps, including limited industry participation, dependence on cross-institutional integration readiness, and the need for clearer regulatory mandates and transition guidelines. These factors suggest that the full-scale implementation of K-CASH will require not only internal institutional preparedness but also decisive regulatory support and broader industry alignment. Furthermore, interview results reveal the emergence of behavioral intention among users to adopt K-CASH once system stability and regulatory clarity are achieved. This study contributes to the literature on technology adoption in capital market infrastructures and provides practical implications for refining the full implementation strategy of K-CASH.